Glutathione and redox signaling in substance abuse - Uys, Joachim D. (Biomed Pharmacother, 2014)
Throughout the last couple decades, the cause and consequences of substance abuse has expanded to identify the underlying neurobiological signaling mechanisms associated with addictive behavior. Chronic use of drugs, such as cocaine, methamphetamine and alcohol leads to the formation of oxidative or nitrosative stress (ROS/RNS) and changes in glutathione and redox homeostasis. Of importance, redox-sensitive post-translational modifications on cysteine residues, such as S-glutathionylation and S-nitrosylation could impact on the structure and function of addiction related signaling proteins. In this commentary, we evaluate the role of glutathione and redox signaling in cocaine-, methamphetamine- and alcohol addiction and conclude by discussing the possibility of targeting redox pathways for the therapeutic intervention of these substance abuse disorders.